Determinants of Incidence of Myofascial Pain Syndrome on Coffee Picker Farmers in Pulu-Pulu Village, North Toraja Regency - Loritma Lasarus; Yahya Thamrin; Atjo Wahyu; Syamsiar S. Russeng; Saifuddin Sirajuddin; Agus Bintara Birawida (Indian Journal of Forensic Medicine & Toxicology, 2022)
Myofascial Pain Syndrome is a muscular pain that are often encountered in humans due to non-ergonomicpositions during daily activities. In addition to the work position, Myofascial Pain Syndrome is also affected byindividual factors and other occupational factors. This study aimed to determine the factors associated with theincidence of Myofascial Pain Syndrome on coffee picker farmers in Pulu-Pulu village, North Toraja Regency. Thiswas a quantitativeresearch with cross sectional study method. Interviews were conducted on 45 respondents whowere coffee picker farmers which was obtained based on the total sampling method. Data regarding sex, age,working period, working duration were measured using questionnaire. Data regarding posture were measuredusing the RULA assessment sheet and data regarding the incidence of myofascial pain syndrome were obtainedthrough doctor’s diagnosis.The data were analyzed using SPSS 21 with the results of Chi Square test showed thatthere was a correlation between gender (p = 0.011), age (p = 0.000), working period (p = 0.017), working duration(p = 0.010), posture (p = 0.019) and the incidence of myofascial pain syndrome. While the Logistic Regression testshowed that the most significant and positive correlation was age and working duration. Writer would kindlysuggest farmers to take breaks periodically while working to relax their body.